Standardized Outcomes in Nephrology—Peritoneal Dialysis (SONG-PD): Study Protocol for Establishing a Core Outcome Set in PD. Issue 6 (November 2017) - Manera, Karine E.; Tong, Allison; Craig, Jonathan C.; Brown, Edwina A.; Brunier, Gillian; Dong, Jie; Dunning, Tony; Mehrotra, Rajnish; Naicker, Sarala; Pecoits-Filho, Roberto; Perl, Jeffrey; Wang, Angela Y.; et al.
Background: Worldwide, approximately 11% of patients on dialysis receive peritoneal dialysis (PD). Whilst PD may offer more autonomy to patients compared with hemodialysis, patient and caregiver burnout, technique failure, and peritonitis remain major challenges to the success of PD. Improvements in care and outcomes are likely to be mediated by randomized trials of innovative therapies, but will be limited if the outcomes measured and reported are not important for patients and clinicians. The aim of the Standardised Outcomes in Nephrology-Peritoneal Dialysis (SONG-PD) study is to establish a set of core outcomes for trials in patients on PD based on the shared priorities of all stakeholders, so that outcomes of most relevance for decision-making can be evaluated, and that interventions can be compared reliably. Methods: The 5 phases in the SONG-PD project are: a systematic review to identify outcomes and outcome measures that have been reported in randomized trials involving patients on PD; focus groups using nominal group technique with patients and caregivers to identify, rank, and describe reasons for their choice of outcomes; semi-structured key informant interviews with health professionals; a 3-round international Delphi survey involving a multi-stakeholder panel; and a consensus workshop to review and endorse the proposed set of core outcome domains for PD trials. Discussion: The establishment of 3 to 5 high-priority core outcomes, to be measured and reported consistently in all trials in PD, will enable patients and clinicians to make informed decisions about the relative effectiveness of interventions, based upon outcomes of common importance.